2011
DOI: 10.3844/jmssp.2011.165.168
|View full text |Cite
|
Sign up to set email alerts
|

A New Cryptosystem Based on Factoring and Discrete Logarithm Problems

Abstract: Problem statement:A cryptosystem allows a sender to send any confidential or private message using a receiver's public key and later the receiver confirms the integrity of the received message using his secret key. Currently the existing cryptosystems were developed based on a single hard problem like factoring, discrete logarithm, residuosity, knapsack or elliptic curve discrete logarithm. Although these schemes appear secure, one day in a near future they may be broken if one finds a solution of a single har… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Thus, the security of the proposed cryptosystem is very stronger than an existing cryptosystems 15,17 since ADV has extra trouble to find out the solutions of CCP and synchronized fractional order chaotic systems.…”
Section: -9mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the security of the proposed cryptosystem is very stronger than an existing cryptosystems 15,17 since ADV has extra trouble to find out the solutions of CCP and synchronized fractional order chaotic systems.…”
Section: -9mentioning
confidence: 99%
“…29 A new fast public key cryptosystem based on two cryptographic assumptions, namely, Diophantine approximation and IFP expected the high level of security of the system. 4 The authors 16,17 have been shown that the multiple cryptographic assumptions offer a greater security level than those schemes based on a single assumption. Therefore, the hybrid mode based cryptosystem provides greater security level while comparing with a single hard problem.…”
Section: Introductionmentioning
confidence: 99%
“…This is due to unlikely solving two hard problems simultaneously. Many public key cryptosystem have been designed based on both IFP and DLP [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] but to design such schemes is not an easy task since many of them have been shown insecure.…”
Section: Introductionmentioning
confidence: 99%
“…Many cryptographers realize it and start to develop a more secure cryptosystem. One of the methods to design such scheme is by using multiple cryptographic assumptions (Ismail et al, 2008a;Elkamchouchi et al, 2004;Harn, 1994;Baocang and Yupu, 2005;Ismail et al, 2008b;Ismail and Hijazi, 2011). The reason behind this is an adversary needs a longer period of time in order to break the multiple cryptographic assumptionsbased cryptosystem since it is very unlikely for the adversary to obtain the solutions of these cryptographic assumptions simultaneously.…”
Section: Introductionmentioning
confidence: 99%